O torcer no futebol como possibilidade de lazer e vínculo identitário para torcedores de América-MG, Atlético-MG e Cruzeiro - Jefferson Nicassio Queiroga de Aquino (2017)
Football and support a team are important elements of Brazilian culture and have been established in the city of Belo Horizonte since the beginning of last century. With regard to that, as part of the Belo Horizontes culture, they are also responsible for the identity construction of this population, emphasizing as an important leisure option. The objective of this study was to investigate the identity and leisure bond of the fans of América, Atletico and Cruzeiro - clubs based in the city of Belo Horizonte and participants of 2016s A series of Brazilian Football Championship. Specifically, sought to compare the profile of organized and unorganized supporters, identify their leisure practices while attending football stadiums in the city of Belo Horizonte, and analyze football assistance as a leisure practice for them. For this, a field research was developed with two parts, the first one being a collection of questionnaires in the vicinity of Belo Horizontes stadiums and the second a semistructured interview conducted with fans selected from the results of the first stage. The analysis of questionnaires data was performed through a descriptive statistical analysis and the interviews data was done a content analysis. After the analysis, it was identified that organized and unorganized supporters differ in age, marital status and participation from fan membership programs, also the former having a higher level of identification with the team than the latter. With respect of leisure activities, it was identified that the participants of the research have a preference for cheering and going to the stadium to follow their teams in the detriment of other options. The data analysis also allowed to identify that the unconditional love of the fan by their team influences in their dedication and leisure time consumption to this activity. In conclusion, the identity construction of the supporter happens through the socio-cultural context in which the individual is inserted and also in the difference from the recognition of the other as rival. We also infer that, for individuals with a high level of identification with the team, cheering can be understood as serious leisure. This research sought to foment discussion in the field of leisure studies by bringing serious leisure theory as a possibility of understanding a certain activity.